A study on the rights of house purchasers in Peninsular Malaysia / Noor Diyana Yahaya, Noorshahida Salim and Muhammad Syaiful Akmal Mohamad Razi - Yahaya, Noor Diyana; Salim, Noorshahida; Mohamad Razi, Muhammad Syaiful Akmal (2007)
On the 13th of April 2007, the Prime Minister of Malaysia, Dato' Seri Abdullah Ahmad Badawi, launched four new initiatives in improving the functions and roles of the local authority regarding a development project. This new launching if any, further enunciate the importance of the housing development industry in Malaysia. It is only expected that one of the biggest industry in Malaysia receives the attention necessary to it. Issues of abandoned housing projects, late delivery of houses, and non-issuance of the Certificate of Fitness are just some of the many problems faced by today's house purchasers. And it is both stirring as well as sad when examining how so many of these unresolved issues has continually affected individuals as well as the society as a whole. For long, issues regarding the housing industries have plagued the country and its citizen. A transaction that appears both normal and simple has proven to cause numerous difficulties among many house purchasers. The Housing Development (Control & Licensing) Act 1966, was introduced to unravel the matter. The purpose of the Act was declared to be for the protection of the house purchasers. This research will examine the many issues pertaining the housing industries, the law guiding it, as well as the individuals affected by it.